2021
DOI: 10.1016/j.wem.2020.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of Oseltamivir Capsules for Pediatric Use on a Long-Term Cruise: A Treatment Option

Abstract: Influenza is a concerning disease in terms of risk management for cruise passengers during a voyage. Currently, cruise passengers include children in addition to elderly people. Oral oseltamivir can be used to treat pediatric influenza. In addition, early antiviral treatment may reduce the spread of influenza on board. However, the capsule form of oseltamivir is not of the recommended dosage for children. In this report, we describe 2 siblings who acquired influenza during travel on a world cruise ship and wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…This study was approved by the institutional ethics committee (institutional review board number 2020–017). Of the study patients, two pediatric patients have previously been reported separately, with a discussion on a potential pediatric treatment option [ 4 ].…”
mentioning
confidence: 99%
“…This study was approved by the institutional ethics committee (institutional review board number 2020–017). Of the study patients, two pediatric patients have previously been reported separately, with a discussion on a potential pediatric treatment option [ 4 ].…”
mentioning
confidence: 99%